Possible evidence for the presence of volatiles on the warm super-earth TOI-270 b - Coulombe, Louis-Philippe; Benneke, Björn; Krissansen-Totton, Joshua; L’Heureux, Alexandrine; Piaulet-Ghorayeb, Caroline; Radica, Michael; Roy, Pierre-Alexis; Ahrer, Eva-Maria; Cadieux, Charles; Miguel, Yamila; Schlichting, Hilke E.; Delgado-Mena, Elisa; et al. (The astronomical journal, 2025)
The search for atmospheres on rocky exoplanets is a crucial step in understanding the processes driving atmosphere formation, retention, and loss. Past studies have revealed the existence of planets interior to the radius valley with densities lower than would be expected for pure-rock compositions, indicative of the presence of large volatile inventories, which could facilitate atmosphere retention. Here, we present an analysis of the JWST/NIRSpec G395H transmission spectrum of the warm ( K) super-Earth TOI-270 b (Rp = 1.306 R⊕), captured alongside the transit of TOI-270 d. The JWST white light-curve transit depth updates TOI-270 b’s density to ρp = 3.7 ± 0.5 g cm−3, inconsistent at 4.4σ with an Earth-like composition. Instead, the planet is best explained by a nonzero, percent-level water mass fraction, possibly residing on the surface or stored within the interior. The JWST transmission spectrum shows possible spectroscopic evidence for the presence of this water as part of an atmosphere on TOI-270 b, favoring an H2O-rich steam atmosphere model over a flat spectrum (, inconclusive to moderate), with the exact significance depending on whether an offset parameter between the NIRSpec detectors is included. We leverage the transit of the twice-larger TOI-270 d crossing the stellar disk almost simultaneously to rule out the alternative hypothesis that the transit light source effect could have caused the water feature in TOI-270 b’s observed transmission spectrum. Planetary evolution modeling furthermore shows that TOI-270 b could sustain a significant atmosphere on gigayear timescales, despite its high stellar irradiation, if it formed with a large initial volatile inventory.
Gesehen am 20.01.2026